LINC317.5 as a novel biomarker for hypertriglyceridemia in abnormal glucose metabolism - Yang, Yixue; Sun, Mengzi; Yan, Shoumeng; Yao, Nan; Li, Xiaotong; Wu, Caihong; Wu, Zibo; Wang, Fengdan; Cui, Weiwei; Li, Bo (Cell death discovery, 2024)
The global rise in prediabetes and diabetes, with type 2 diabetes (T2DM) being predominant, highlights the association between T2DM and hypertriglyceridemia (HTG). Patients with both abnormal glucose levels and HTG require increased attention due to higher risks of complications and mortality. Therefore, this study aimed to find the key long non-coding RNA (lncRNA) of HTG in the abnormal glucose metabolism patients. We collected blood samples for RNA sequencing experiments and blood samples for validation in population. We have conducted RNA sequencing, weighted gene co-expression network analysis (WGCNA), quantitative real‐time polymerase chain reaction (qRT-PCR) in a 82-vs-82-sample-size population and insulin induced HepG2, RNA- Fluorescence in situ hybridization (FISH) and Cell Counting Kit-8 (CCK-8). We also explored lipid metabolism related transcription factor and the related protein expression and processed key lncRNA by both interference expression and overexpression, and the related consequences were rescued by its target mRNA. ENST00000540317.5 (LINC317.5) was lower in HTG with abnormal glucose metabolism and was found in both cytoplasm and nucleus in HepG2, inversely regulating the accumulation of TG and its target mRNA TKFC . Relative expression of peroxisome proliferator-activated receptor alpha ( PPARα) and peroxisome proliferator-activated receptor gamma ( PPARγ) were decreasing, and SREBP-1c (sterol regulatory element-binding protein-1c) was increasing of the interference expression of LINC317.5. Interference expression of LINC317.5 significantly decreased the protein expression of ACADM and CPT1A , whereas increased the protein expression of FAS and ACC1 . TKFC partly reduced the triglyceride (TG) accumulation of LINC317.5. In conclusion, we suggested LINC317.5- TKFC as a key for TG accumulation in the HepG2-insulin resistant (IR). These might provide information of non-invasive biomarkers for the HTG with abnormal glucose.